2010
DOI: 10.1128/aem.02726-09
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and Multivariate Analyses To Determine the Effects of Different Tillage and Residue Management Practices on Soil Bacterial Communities

Abstract: Bacterial communities are important not only in the cycling of organic compounds but also in maintaining ecosystems. Specific bacterial groups can be affected as a result of changes in environmental conditions caused by human activities, such as agricultural practices. The aim of this study was to analyze the effects of different forms of tillage and residue management on soil bacterial communities by using phylogenetic and multivariate analyses. Treatments involving zero tillage (ZT) and conventional tillage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(93 citation statements)
references
References 62 publications
9
79
3
2
Order By: Relevance
“…Tillage treatment effects were less pronounced at the 5-15 cm depth. These observations are in agreement with previous findings reported by, for example, Ceja-Navarro et al [35], Drijber et al [36], Ekenler and Tabatabai [37], Feng et al [12], Helgason et al [13], and Ibekwe et al [15]. Total PLFAs in the no-till surface soil were much higher than those reported in a previous study during the fallow period [12] conducted on the same soil type although organic carbon contents at the two sites were similar.…”
Section: Discussionsupporting
confidence: 51%
“…Tillage treatment effects were less pronounced at the 5-15 cm depth. These observations are in agreement with previous findings reported by, for example, Ceja-Navarro et al [35], Drijber et al [36], Ekenler and Tabatabai [37], Feng et al [12], Helgason et al [13], and Ibekwe et al [15]. Total PLFAs in the no-till surface soil were much higher than those reported in a previous study during the fallow period [12] conducted on the same soil type although organic carbon contents at the two sites were similar.…”
Section: Discussionsupporting
confidence: 51%
“…in different soil management and crop rotation systems, observing that, in regard to the soil management system, the number of isolates obtained on the no-tillage system was very similar to the number obtained in the conventional tillage system, 51 and 49 % respectively. In contrast with this study, Ceja-Navarro et al (2010) observed that the Pseudomonadales group, represented mainly by fluorescent Pseudomonas sp., was favored mainly by treatments in which crop residues were maintained, both in the conventional and the no-tillage systems. However, these microorganisms were negatively affected by the no-vegetation treatment.…”
Section: Management Systemcontrasting
confidence: 52%
“…The differences in silt and sand fraction under zero tillage suggest that it was a safer agriculture treatment to improve and preserve soil microbial diversity Significance of taxonomic and phylogenetic similarity between pairwise tillage treatments (CPT and ZT, CPT and PT, ZT and PT) were tested. * 0.01 < P < 0.05, ** P < 0.01, ns not significant, PT plow tillage, ZT zero tillage, CPT chisel plough tillage (Ceja-Navarro et al 2010), leading to higher nutrient levels (organic carbon) than plow tillage was in our study. This can explain why larger differences in both bacterial polygenetic and taxonomic diversity were found between the zero tillage and plow tillage (Fig.…”
Section: Tillage Treatment Contributes To Differences In Soil Charactmentioning
confidence: 68%
“…Numerous studies have focused on how microbial abundance and structure are affected by reduced tillage and have indicated that soil organic carbon is a majority factor modifying the soil microbial community (Ceja-Navarro et al 2010;Pastorelli et al 2013). However, a few studies have shown that conservation tillage enhances soil carbon sequestration, but these reports have described changes in microbial biomass and diversity in northern China that account for approximately 56 % of the Chinese land area, only using indirect techniques (Chen et al 2009;Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%